Occurrence of ventricular septal perforation in patients with permanent left bundle branch pacing followed up using echocardiographic and computed tomography images. Issue 6 (10th September 2022) - Li, Qiaoyuan; Dai, Wenlong; Fang, Dongping; Ma, Weili; Lin, Cancan; Lu, Chunshan; He, Dongfang; Liu, Xu; Guo, Chengjun
Abstract: Objective: To explore short‐term changes after left bundle branch pacing (LBBP) using echocardiography and computed tomography (CT), especially for postoperative ventricular septal perforation. Methods: Between January and September 2019, 33 patients with atrioventricular block underwent LBBP at Beijing Anzhen Hospital. All the patients were evaluated using electrocardiography, pacing, parameters and echocardiographic measurements, including for major complications, during the 1, 3, 6, 12 and 24‐month follow‐up. Interval perforations were examined during a 1‐month follow‐up echocardiogram and CT. Results: Left bundle branch pacing was successfully performed in 100% (33/33) of patients. The mean seizure threshold was stable and unchanged postoperatively at the 1, 3, 6, 12 and 24‐month follow‐up. The paced QRS duration of the LBBP was 119.72 ± 2.53 ms and <130 ms in all patients. Unipolar impedance during the procedure was higher than 500 Ω (662.00 ± 181.50 Ω). No ventricular septal perforation occurred at the end of the procedure. At the 1‐month follow‐up, two patients reported transthoracic echocardiography, with CT revealing septal lead perforation. Through CT, two other patients were found to have septal lead perforation, and echocardiography indicated that the pacing lead had penetrated the interventricular septum and entered the left subendocardium. At the 1, 3, 6, 12 and 24‐month follow‐up, these four patients exhibited no significant increase in pacing threshold or impedance ( p > .05). No ventricular thrombus or stroke was detected. Conclusion: Permanent LBBP is safe and feasible in patients with bradycardia. Echocardiography and/or CT can more accurately evaluate changes in cardiac structure and function after LBBP. Abstract : Follow‐up of patients with permanent LBBAP evaluated by echocardiography and computed tomography. This study evaluated 33 patients with atrioventricular block using echocardiography and computed tomography for a 24‐month follow‐up after they underwent permanent left bundle branch area pacing (LBBAP). The results suggested that permanent LBBP is safe and feasible in bradycardia patients, and echocardiography and/or computed tomography (CT) scan can more accurately evaluate changes in cardiac structure and function after LBBAP.